Pengaruh Struktur Modal, Profitabilitas, Dan Growth Terhadap Nilai Perusahaan (Studi Kasus Pada Perusahaan Sub Sektor Basic Material Yang Terdaftar Dibursa Efek Indonesia) Periode 2021-2023: (Studi Kasus pada Perusahaan Sub Sektor Basic Material yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023) - Wulandari, Putu Crystina; Dewi, Putu Eka Dianita Marvilianti (Vokasi : Jurnal Riset Akuntansi, 2025)
This study aims to examine the effect of capital structure, profitability, and company growth on firm value in the basic materials sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2021– 2023. This research is a quantitative study with an associative approach. The data used are secondary data in the form of annual financial statements from 33 selected companies using purposive sampling, with an observation period of three years, resulting in a total of 99 observations. The data analysis was conducted using multiple linear regression. The results show that: (1) capital structure has a positive and significant effect on firm value, (2) profitability has a positive and significant effect on firm value, and (3) company growth has a negative but not significant effect on firm value. These findings are expected to serve as a consideration for company management and investors in making strategic decisions and as a reference for future research to include additional variables and extend the observation period to obtain more comprehensive results.